Terroir wine festival visitors: uncorking the origin of behavioural intentions. Issue 5 (4th March 2021) - Kruger, Martinette; Viljoen, Armand
ABSTRACT: Orientation: Wine festivals and events not only attract visitors, but also play a vital role in creating exposure to regional wines and wineries, increasing regional wine sales and stimulating wine tourism. Research design, approach and method: For this quantitative research, a visitor survey was conducted at a regional wine festival in South Africa. Following a convenience sampling method, 473 completed visitor questionnaires were obtained. Research purpose: This research aimed to identify the determinants of three key behavioural intention factors, namely: wine tourism sharing and affiliation, festival loyalty and regional wine appreciation, as well as wine purchasing and regional wine recommendation through a set of three linear regression analyses were performed, which included each of the three behavioural intention factors as separate dependent variables. The independent variables included motives to attend the festival and wine preference attributes Main findings: The results showed a different set of statistically significant determinants for increasing each of the three dependent variables In all three cases the behavioural intention factors were also statistically significant, indicating a strong relationship between the factors. Implications: Festival organizers can use the findings, destination managers, as well as regional wineries/estates to increase regional wine purchases and positive referrals regarding the wine region.